Translation Strategies of English Idiomatic Expression in The Shawshank Redemption Movie Subtitle - Pangestu, Difatrialdi Muji; Mahyuni, Mahyuni; Wilian, Sudirman (Jurnal Ilmiah Profesi Pendidikan, 2022)
The Shawshank RedemptionÂ movie is a meaningful movie which needs to knows more about. The objective of this research is to examine the translation strategy of idiomatic expressions used by the translator in The Shawshank Redemption movie subtitle. The data is obtained by watching closely The Shawshank Redemption movie repeatedly, note-taking, compare the idiomatic expression used by the characters and its translation strategies in the subtitle from the movie. The data that has been collected is translates using Bakerâ€™s Theory but descriptively outlined. The result of this research showed that there are 19 utterances of idiomatic expressions found in The Shawshank Redemption movie based on Seidl and McMordieâ€™s (1988). All of 19 idiomatic expressions are classified based on Bakerâ€™s (1992) translation strategies into 4Â idioms of similar meaning and form, none ofÂ idioms of similar meaning but dissimilar form, 10 translations by omission, and 5 translations by omission.